The Use of Accounting Software to Enter Business Transactions by Students at Ricci 1 Junior High School, Jakarta, Indonesia - Nastasya Cindy Hidajat (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This community service activity was conducted to address junior high school students’ limited understanding of simple business transactions and their unfamiliarity with accounting software for recording transactions. The activity aims to provide an introductory understanding of basic accounting concepts, the importance of recording transactions, and the functions of accounting software, thereby strengthening students’ financial and digital literacy. Method: The activity was held in person at SMP Ricci 1 Jakarta on Friday, March 6, 2026, and lasted 120 minutes, with 29 students participating. The methods used included participatory education through interactive lectures, guided demonstrations, simple case studies, Q&A sessions, quizzes, and feedback questionnaires. Results and Discussion: Before the intervention, the students did not understand the concept of business transactions and were unfamiliar with computerized accounting. After the activity, the students were able to identify simple transactions, understand the importance of record-keeping, and recognize the role of accounting software in managing financial information. Implications: This initiative helps improve financial and digital literacy from an early age. Similar programs should be developed on an ongoing basis, with the curriculum tailored to students' characteristics.